Estimating seasonal fragrant rice production in Thailand: A review article - Kaeomuangmoon, T.; Jintrawet, A.; Katzfey, J. (International Journal of Agricultural Technology, 2019)
The article is reviewed the current and existing methods of fragrant rice crop yield and production forecasts in Thailand and their potential application for seasonal prediction. While several government agencies have carried out the forecast task, however, the further research is needed in order to minimize risk and maximize efficiency of agricultural resources. Incorporation of emerging methods could lead to a new strategy to forecast yields and production as well as to provide timely and reliable forecasts, by adopting integrated agro-informatic tools. The manual crop cutting, end-of-season farmer surveys, remote sensing, spatial databases and decision support system tools and simulation models were reviewed. We concluded that the spatial databases and climate and crop simulation models provided the opportunities to establish an inclusive and integrated platform for farmers, government agencies and private firms to participate in the important task of seasonal forecasting for fragrant rice production systems in Thailand.